Compared With Girls, Boys' Psychological Symptoms Are More Likely to Be Influenced by Lifestyle in Chinese Middle School Students - Lu, Jinkui; Tan, Chun; Zhou, Jianfeng; Sha, Mian; Xu, Yongli; Qiu, Jianhua; Liu, Ningling (Frontiers in Psychology, 2022)
Purpose: To explore the relationship between Chinese middle school students' lifestyles and psychological symptoms and compare the differences between genders. Method: Using the method of stratified cluster sampling, 14,356 students aged 13-18 years from 8 cities in China were selected as participants. the Multidimensional Sub-health Questionnaire of Adolescents was used to estimate psychological symptoms. Chi-square test and Logistic regression analysis were used to analyze the relationship between lifestyle and psychological symptoms. Results: The psychological symptom detection rate of Chinese middle school students was 21.37%. The detection rate of psychological symptoms for boys was 22.1%, which was significantly higher than for girls (20.64%, χ2=4.608，P＜0.05). According to the Logistic regression analysis, factors that have a positive correlation with the demonstration of psychological symptoms (P＜0.01) include: how the students go to school (by foot or on the vehicle) (OR = 1.16，95% CI: 1.07 ~ 1.25); inadequate time for sleep (OR = 1.48，95% CI: 1.28~1.72); video watching time ≥2h/d (OR = 1.25，95% CI: 1.13 ~ 1.39); never exercise (OR = 2.39，95% CI: 2.07 ~ 2.76); never participate in extracurricular exercises (OR = 1.45，95% CI: 1.27 ~ 1.66); have breakfast occasionally (OR=1.35，95%CI:1.22~1.50); never have breakfast (OR = 1.90，95% CI: 1.62 ~ 2.24); always have snacks (OR = 1.27，95% CI: 1.13 ~ 1.44); always drink sugared beverages (OR = 1.37，95% CI: 1.22 ~ 1.55); picky with food occasionally (OR = 1.22，95% CI: 1.11~1.33); Conclusions: There was a positive correlation between unhealthy lifestyle and the occurrence of psychological symptoms, and boys are more easily influenced by lifestyles than girls.